Entrepreneurship Interest Training Through Innovation and Creativity for Generation Z at Sultan Agung Private High School - Kevin Indajang; Hery Pandapotan Silitonga; Ruth Tridianty Sianipar; Juan Anastasia Putri; Lenny Dermawan Sembiring; Acai Sudirman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Innovation and creativity in this digital era are needed in developing the business you want to be involved in so that you are not trapped in daily operational activities and pursuing performance targets. The fundamentals of implementing this service with the theme of training interest in entrepreneurship through innovation and creativity for generation Z at Sultan Agung Private High School are to encourage generation Z, especially in the Sultan Agung Private High School environment, to increase knowledge related to entrepreneurship by utilizing innovation abilities and creativity in developing businesses. The method used in implementing this activity is through lectures and FGD (group discussion forum). The stages of implementing this event include opening and introducing entrepreneurial innovation and creativity, explaining the fundamentals of being an entrepreneur, explaining several problems often faced by young entrepreneurs, then continued with discussions related to new business development. After the service activities are completed, follow-up interviews are conducted regarding the impact of implementing the service activities. According to the interview results, it is known that the understanding of generation Z, especially students at Sultan Agung Private High School, regarding increasing understanding of innovation and creativity has increased by 95%.